Component model for pull-out behaviour of headed anchored blind bolt within concrete filled circular hollow section. (1st October 2017) - Oktavianus, Yusak; Chang, Hongfei; Goldsworthy, Helen M.; Gad, Emad F.
Highlights: A component model for the pull-out behaviour of HABBs from CFCHS tubes is developed. The nonlinear behaviour of each component is identified and assembled. The load transfer and failure sequences of the HABBs in a CFCHS tube are discussed. Procedures are proposed for the assembly of the component springs. Abstract: This paper presents a simplified approach to estimate the pull-out behaviour of headed anchor blind bolts (HABB) from concrete filled circular hollow section (CFCHS). The approach was developed based on a multi-linear component spring model representing the behaviour of the blind bolt's components, i.e. the bolt's shank, the embedded head, and the washer bearing on the inside of the tube wall. Extensive finite element analyses (FEA) were used to develop and calibrate the nonlinear behaviour of each component for monotonic loading only, in which the yield and ultimate strength, as well as the initial and secant stiffness of each component were taken into account. Important parameters such as the diameter of the HABB, diameter and thickness of the circular hollow section (CHS), embedment depth of the embedded head, and concrete strength are also incorporated in defining the component spring behaviour. The proposed method was able to yield a good match with both the FEA and test results for the individual component behaviour in terms of the initial and secant stiffness as well as the ultimate strength. Moreover, the load transfer and failure sequences of the HABB within a CFCHS are discussed, and the assembly procedures of the component springs are proposed, by which the combined component behaviour is identified and matches well with both the FEA and test results.